2007
DOI: 10.1161/01.atv.0000261570.85983.4f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Derived From Beating Heart Mediates Coronary Microvascular Dilation During Tachycardia

Abstract: Objective-Coronary flow is closely correlated to the myocardial metabolic demand. We tested the hypothesis that hydrogen peroxide (H 2 O 2 ) derived from beating hearts mediates metabolic coronary microvascular dilation. Methods and Results-We used a bioassay method in which an isolated microvessel is placed on a beating heart to detect myocardium-derived vasoactive mediators. A rabbit coronary arterial microvessel (detector vessel [DV], nϭ25) was pressurized and placed on a canine beating heart. After intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Pacing the dog heart induced a catalase-inhibitable dilation in the overlying rabbit arteriole, suggesting a role for H 2 O 2 in metabolic dilation. Similar support for a role for H 2 O 2 was observed in an in vivo dog model, where pacing-induced epicardial coronary arteriolar dilation was observed during increases in metabolism 4, 5 .…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Pacing the dog heart induced a catalase-inhibitable dilation in the overlying rabbit arteriole, suggesting a role for H 2 O 2 in metabolic dilation. Similar support for a role for H 2 O 2 was observed in an in vivo dog model, where pacing-induced epicardial coronary arteriolar dilation was observed during increases in metabolism 4, 5 .…”
supporting
confidence: 76%
“…The resulting dilation was shown to be catalase-sensitive and related to the metabolic rate of the cultured myocytes 2 . A variation of that preparation was employed by Shimokawa’s laboratory, where pressurized coronary arterioles from a rabbit were placed on a canine beating heart 4 . Pacing the dog heart induced a catalase-inhibitable dilation in the overlying rabbit arteriole, suggesting a role for H 2 O 2 in metabolic dilation.…”
mentioning
confidence: 99%
“…One potential, but untested, mediator of reactive hyperemia is H 2 O 2 , which we previously demonstrated (43,44,47) mediates coronary metabolic vasodilation via K V channels. The role of H 2 O 2 in metabolic vasodilation has recently been confirmed by others (32,55), but the hypothesis that H 2 O 2 functions in reactive hyperemia remains to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 79%
“…This means that the burst formation of superoxide after reperfusion (Zweier, 1988) is dismutated to hydrogen peroxide selectively by SOD m . It has also been reported that hydrogen peroxide can dilate vasculature in the heart and cause an increase of tissue blood perfusion (Burgoyne et al, 2007; Kokusho et al, 2007; Yada et al, 2008). To test whether hydrogen peroxide contributes to this transient peak of tissue Po 2 after the treatment of SOD m , we performed EPR oximetry on the wild-type mice treated with EUK134, which is a superoxide dismutase mimetic with catalase activity (Izumi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%